Factors Influencing the Performance of Sarawak Local Authorities - Abdul Hamid, Siti Mardinah; Hamali, Jamil; Abdullah, Firdaus (Universiti Teknologi MARA Cawangan Sarawak, 2021)
This paper presents the empirical research on factors that influenced the performance in Local Authorities in Sarawak. It explores the benefits of performance measure and discusses the factors that influenced the performance for Local Authorities in providing an excellent service delivery in accordance with the vision to provide a world class standard of civil service in Sarawak. Additionally, this paper highlights issues affecting the performance of Local Authorities and their usage in performance management. Findings from this study could assist in the identification of factors that notably have an impact on performance and provide recommendations that would efficaciously enhance the performance for Local Authorities in Sarawak